2018
DOI: 10.1063/1.5042207
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline (C3N) nanoribbons: Magnetic metal, semiconductor, and half-metal

Abstract: Two-dimensional polyaniline sheet has been recently synthesized and found that it is a semiconductor with indirect band gap. Polyaniline nanoribbons decomposed from two-dimensional polyaniline sheet (C 3 N sheet) are investigated using density functional theory. The existence of nitrogen atoms in the edge of the ribbons increases stability and magnetization of the ribbons and make them different from graphene nanoribbons. Unsaturated nanoribbons are magnetic metals so that armchair C 3 N nanoribbons are gap-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Bilayer C 3 N shows anisotropic carrier mobility [30] and high thermal conductivity [31]. We studied C 3 N nanoribbons and found that some of them can be half-metal [32].…”
Section: Mahmood Et Al Has Recently Synthesized a New 2d Planner Matmentioning
confidence: 99%
“…Bilayer C 3 N shows anisotropic carrier mobility [30] and high thermal conductivity [31]. We studied C 3 N nanoribbons and found that some of them can be half-metal [32].…”
Section: Mahmood Et Al Has Recently Synthesized a New 2d Planner Matmentioning
confidence: 99%
“…On the other side, for thermally insulating and thermoelectric materials, a component with the minimal thermal conductivity is more suitable to reduce the energy losses or to improve the thermal to electric energy conversion efficiency, respectively. Accordingly the accurate evaluation of a material's thermal conductivity is a fundamental issue for benchmarking relevant materials for a given application purpose [5][6][7][8][9][10][11]. While for the bulk materials there exist various experimental ways for estimating the thermal conductivity, when the size of the materials decreases and approach the nanoscale, this can turn into a challenging and complicated task.…”
Section: Introductionmentioning
confidence: 99%
“…These 2D lattices were also found to show strain-tunable band gap, which is desirable for sensing applications. The optical and electronic properties of these novel 2D systems were also explored in the several recent theoretical works [23][24][25][26][27][28][29][30][31][32]. In general, theoretical studies offer unique tools to investigate the material properties of 2D based materials [33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%